(3cfR GdCSQGQ hdhGbM GdCacGQs - (3YHO GdQMef Hf SYjO GdUfgGLj, GHf ebTGH GdUfgGLjs
(3ChdgG (B:s
(3hdcG cGf GdfXQ hGdEYJHGQ ajeG CHQYJg ef CLfGS GdehLhOGJ hCfhGY GdeNdhbGJ s
(3BNQgG (B:s
(3jG QH ajbhd dG YWjfce GaVd ef Pdc ajbhdhf hCi TF CaVd ef Pdc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B384s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs